Language ability - Nečiūnas, V. (Psichologija, 1968)
This article explores some of the features of language abilities.Based on experiments and other research methods the collected material, the author claims that verbal memory productivity is an important component of language abilities.Two main types of language mastery emerge during foreign language learning: concrete and analyzing, which determine the typological features of students, the first and second signal systems interaction distinctions.Domination in comparative individual signaling systems also plays an important role in shaping students' active interests their subjects.The role of leadership in comparative signaling systems and their strength forming language abilities is worthy of further study.
Keywords: language abilities; signaling system; verbal memory